Effect of supplementing teff straw with different levels of leucaena or sesbania leaves on the degradabilities of teff straw, sesbania, leucaena, tagasaste and vernonia and on certain rumen and blood metabolites in Ethiopian Menz sheep - Bonsi, M.L.K.; Osuji, P.O.; Tuah, A.K. (Elsevier, 1995)
In vitro gas production, dry matter and nitrogen degradabilities of fresh and sun-dried foliages of four fodde trees (FTs) (Sesbania sesban, Leucaena leucocephala, Chamaecytisus palmensis (tagasaste), Vernonia amygdalina) and of teff straw were estimated. In Experiment 1, feed samples were incubated in three different rumen environments (ecologies) created by feeding sheep the following: teff straw, teff straw plus 174 g dry matter (DM) od sesbania or with 117, 175 or 232 g DM day minus one of leucaena. Gas production constants were estimated. Rumen fluid was sampled at 3, 6, 9, 12 and 24 h after feeding in Experiment 2 and PH, NH3-N, volatile fatty acids (VFAs) and minerals determined. Plasma urea nitrogen (PUN) concentrations were estimated in blood taken from the sheep at 3, 6, 9 and 12h. Drying relatively increased the neutral detergent fibre (NDF), acid detergent fibre (ADF) and NDF-nitrogen concentrations in all foliages except in leucaena. Dry sesbania, tagasaste and vernonia had lower nitrogen concentrations than the fresh ones but the opposite trend was observed for leucaena. Dry matter disappearance (DD) at incubation times of 3-48 h and degradation constants differ among the four foliages. Compared with the other foliages, sesbania had lower fibre fractions and degraded faster. Drying of foliages reduced degradability. Supplementation did not affect the DD of fresh foliages but enhanced the rate of DD of dry foliages. There was no feed type X rumen ecology interaction for either dry or fresh foliages. The rate of teff straw degradation in sheep fed supplemented diets was increased. Gas production was lower in dry than in fresh foliage. Gas production values for dry foliages were: sesbania, 55.5; tagasaste, 54.5; vernonia, 49.5; leucaena, 45. Corresponding values for fresh foliages were tagasaste, 81.8; sesbania, 62.7; leucaena, 51.1; vernonia, 51. The rates of gas production were highest for dry tagasaste (0.0779), followed by sesbania (0.0718), leucaena (0.0563) and vernonia (0.0477). Corresponding values for fresh foliages were; leucaena, 0.0541; tagasaste, 0.0528; sesbania, 0.0478; vernonia, 0.0366. Supplementation increased levels of all rumen metabolites measured. Rumen NH3-N was highly correlated with PUN. Correlations among the other metabolites were either low or negative. The results are discussed in relation to the chemical composition, type and form of fodder tree and the rumen ecology resulting from feeding these foliages.